Neuropsychological correlates of dominance, warmth, and extraversion in neurodegenerative disease - Sollberger, Marc (2011)
INTRODUCTION: Changes in personality differ qualitatively and quantitatively between patients with different neurodegenerative diseases, likely due to divergent patterns of regional neurodegeneration. Regional damage to circuits underlying various cognitive and emotional functions have been associated with interpersonal traits like dominance, extraversion, and warmth in patients with neurodegenerative diseases, suggesting that personality may in part be mediated by these more basic neuropsychological functions. In this study, we hypothesized that different combinations of cognitive, neuropsychiatric, and emotional measures would predict different interpersonal traits in patients with neurodegenerative diseases. METHODS: A battery of cognitive, neuropsychiatric, and emotional measures was administered to 286 patients with various neurodegenerative diseases such as Alzheimer’s disease, behavioral variant frontotemporal dementia, semantic dementia, and progressive supranuclear palsy, and informants described patients’ dominance, extraversion, and warmth using the Interpersonal Adjective Scales (IAS) personality questionnaire. Regression modeling was performed to identify which neuropsychological factors uniquely predicted current personality, controlling for age, gender, and premorbid personality. RESULTS: Social dominance covaried with patients’ capacity for cognitive control and verbal fluency. Conversely, warmth did not rely on these executive or verbal skills, but covaried primarily with patients’ capacity for emotional responsiveness. Extraversion, representing a blend of dominance and warmth, demonstrated an intermediate degree of relationship to both executive/verbal and emotional functions. CONCLUSIONS: These findings suggest that different personality traits are partly subserved by specific cognitive and emotional functions in neurodegenerative disease patients. While this study was performed in the context of brain damage, the results raise the question of whether individual differences in these neuropsychological abilities may also underlie variability in normal personality.